Investigation of the relationship between exercise addiction and self-esteem on psychological health in former male athletes - Sermin Agrali Ermis; Gunseli Duman (Journal of Men's Health)
Background: Exercise addiction can significantly affect the psychological and physical health of male athletes and may be associated with self-esteem. Professionals working in sports organizations are often required to maintain high levels of physical activity, which may influence these factors. This study aimed to examine the relationship between exercise addiction and self-esteem in former male athletes, considering demographic variables. Methods: This cross-sectional study comprised 301 male individuals employed in sports organizations, with a mean age of 34.85 years. A relational survey model was used to examine the associations between exercise addiction, self-esteem and demographic factors. The data were collected through online surveys, utilizing the Rosenberg Self-Esteem Scale and the Exercise Addiction Scale, and statistical analyses included descriptive statistics, independent t-tests, (analysis of variance) ANOVA and correlation analyses. Results: The findings revealed that self-esteem was positively correlated with age and income level (p < 0.05), with higher self-esteem observed in individuals with greater income and longer engagement in sports. Additionally, individuals who had participated in sports for a longer duration exhibited higher levels of exercise addiction. Conclusions: These findings indicate that demographic characteristics play a significant role in shaping self-esteem and exercise addiction in former athletes. Interventions aimed at enhancing psychological well-being and behavioral health in sports professionals should be tailored to account for individual demographic factors to maximize their effectiveness.